Treatment of petrochemical wastewater with low C/N by IFFAS-ESMBR integrated composite process - ZHAO Xuan; LIU Tao; YANG Meng; QIAO Sen (Gongye shui chuli)
A new integrated composite process(IFFAS-ESMBR) based on integrated free floating biofilm-activated sludge(IFFAS) and electrochemical sequence membrane bioreactor(ESMBR) was constructed, which enhanced the biological treatment performance of low C/N petrochemical wastewater with the help of bioelectrochemical system and membrane filtration. The results showed that for the treatment of low C/N actual petrochemical wastewater (COD/TN=4.3∶1, COD 1 969 mg/L, TN 460 mg/L), the average removal rates of COD, NH4+-N, and TN by this composite process during stable operation could reach 98.1%, 91.3%, and 89.1%, respectively. Under the applied voltage of -1.2 V, the average growth rate of transmembrane pressure difference(TMP) of CNT-PVDF composite hollow fiber membrane was only 2.5 kPa/d, and the PN/PS of sludge on the membrane surface decreased gradually, indicating that the degree of irreversible membrane fouling was mild. 16S rRNA high-throughput sequencing showed that a large number of carbon and nitrogen removal functional bacteria, such as Rhodobacterales, Verrucomicrobiales, Anaerolineales and Xanthomonadales, were enriched in suspended sludge, membrane surface sludge and carrier surface sludge, which played a significant role in the degradation of organic matter and ammonia nitrogen in the reactor. In addition, a large number of nitrifying and denitrifying bacteria such as Nitrosomonadales and Burkholderiales were enriched on the surface of the carrier, which further confirmed high TN removal efficiency of the reactor. The results could provide reference for the enhanced biological treatment process of petrochemical wastewater with low C/N.